The use of biological grafts for reconstruction of the inferior vena cava is a safe and valid alternative: results in 32 patients in a single institution. Issue 8 (18th January 2013) - Pulitanó, Carlo; Crawford, Michael; Ho, Phong; Gallagher, James; Joseph, David; Stephen, Michael; Sandroussi, Charbel
Abstract: Background: Resection and reconstruction of the inferior vena cava (IVC) is occasionally required in the surgical treatment of intra‐abdominal tumours. IVC reconstruction can be performed with biological or synthetic graft material, with most centres preferring synthetic grafts. In spite of the potential advantages of biological grafts in terms of handling characteristics, and safety, very limited data are available about their use in patients requiring an IVC resection. Methods: Medical records of 32 patients who underwent an IVC resection and reconstruction from 1990 and 2011 with autogenous peritoneo‐fascial ( N = 22) and bovine pericardial ( N = 10) grafts were reviewed. Results: A tangential resection with patch repair was performed in 10 patients, whereas in the remaining 22 it was necessary to resect and replace a segment or all of the retrohepatic IVC. A concomitant liver resection was performed in 14 patients, nephrectomy in 10 and pancreaticoduodenectomy in 2 patients. There were no acute or late complications related to graft thrombosis or infection. Three patients died as a consequence of multi‐organ failure. Overall survival at 1 and 5 years was 78% and 48%, respectively. Conclusions: The preferential use of synthetic grafts in IVC replacement is not evidence based. Selection of an appropriate prosthetic graft for IVC reconstruction should be based on the safety and its handling features. The use of biological grafts for IVC repair is a valid alternative to current synthetic materials and may in fact be superior in terms of biocompatability, ease of handling, reduced rate of infection and improved long‐term patency without permanent anticoagulation.